2010
DOI: 10.5042/eihsc.2010.0145
|View full text |Cite
|
Sign up to set email alerts
|

Raising silenced voices: South Asian women immigrating after marriage

Abstract: This paper looks at the experiences of first‐generation South Asian women who entered the UK to marry and then suffered domestic violence. It is based on an innovative and collaborative trans‐national project, carried out in two stages. In the first stage, a range of immigrant South Asian women, who had experienced domestic violence, were consulted. This consultation aimed to ascertain what they believed would have been useful information, if available prior to immigration, about the UK and the life they might… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 10 publications
0
16
0
Order By: Relevance
“…Gender as a symbolic institution prescribes what is expected of a woman in her roles (i.e., submissive behavior, marriage obligation, male superiority), which shapes the kind and extent of individual and social support that women receive if they do not act in the roles expected of them [ 24 26 ]. On the one hand, close family ties in the family of origin, extended family and family of in-laws can result in positive social support for a woman [ 26 31 ]. On the other hand, such support is constrained by concomitant values of family privacy, unit, and maintenance of the family’s reputation [ 24 26 ], which means that individual family members frequently subordinate their needs to ensure family solidarity, which for some women might mean tolerating abuse [ 25 , 26 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Gender as a symbolic institution prescribes what is expected of a woman in her roles (i.e., submissive behavior, marriage obligation, male superiority), which shapes the kind and extent of individual and social support that women receive if they do not act in the roles expected of them [ 24 26 ]. On the one hand, close family ties in the family of origin, extended family and family of in-laws can result in positive social support for a woman [ 26 31 ]. On the other hand, such support is constrained by concomitant values of family privacy, unit, and maintenance of the family’s reputation [ 24 26 ], which means that individual family members frequently subordinate their needs to ensure family solidarity, which for some women might mean tolerating abuse [ 25 , 26 ].…”
Section: Resultsmentioning
confidence: 99%
“…The papers that touched on ethnicity and minority-based structural violence noted that minority women lacked knowledge of laws existing to support them from abuse, availability of resources, and their entitlements to services [ 24 ]. The literature identified the need for culturally appropriate services [ 25 , 60 ], limited availability of translators [ 31 ] and lack of services in their first language [ 24 ]. Some papers reported that immigrant women experienced reasons to distrust welfare institutions [ 24 ], culturalization (e.g., assumed cultural acceptance of wife abuse) [ 46 , 60 , 70 ], and racism and discrimination [ 53 ].…”
Section: Resultsmentioning
confidence: 99%
“…The parents of the brides and the brides themselves need to be vigilant about these issues. The craze for NRI grooms must perhaps be overcome (see also Hague et al, 2010). It is important to check the NRI groom's personal information particulars such as marital status, employment details, qualification and post, salary, address of office, employer and their credentials, financial status, properties owned, social security number, immigration status, type of visa, and eligibility to take a spouse to the other country (NCW, http://ncw.nic.in/; MOIA, http:// www.moia.gov.in).…”
Section: State Interventions and Law Reform Initiativesmentioning
confidence: 99%
“…It is important to check the NRI groom's personal information particulars such as marital status, employment details, qualification and post, salary, address of office, employer and their credentials, financial status, properties owned, social security number, immigration status, type of visa, and eligibility to take a spouse to the other country (NCW, http://ncw.nic.in/; MOIA, http:// www.moia.gov.in). Above all, women should be equipped with information about laws and rights by encouraging migrating women to attend events and seminars to acquaint them with the resources available in a foreign land and to provide essential information to protect their rights (Hague et al, 2010). In conclusion, a crucial need of the hour is changes in national and international advocacy, law, and policy, all of which are required to ensure justice and a viable life, especially to women in this situation.…”
Section: State Interventions and Law Reform Initiativesmentioning
confidence: 99%
“…While some respondents mentioned the existence of pressure from the community on Portuguese women to accept violent behaviour, this did not seem to operate in the same way as it did for other immigrant communities, for example, where issues of family honour are more prevalent (see Wellock, 2008, Hague et al, 2010, Kallivayalil, 2010. Most respondents mentioned a generalised sense of shame as the explanation for the apparent inaction of Portuguese women towards domestic violence, rather than shame associated with loss of reputation for the whole family, as the term 'family honour' would indicate.…”
Section: Shame and Community Pressurementioning
confidence: 99%